PACAP Is Lethal to Flavobacterium psychrophilum Through Either Direct Membrane Permeabilization or Indirectly, by Priming the Immune Response in Rainbow Trout Macrophages - Semple, Shawna L.; Rodríguez-Ramos, Tania; Carpio, Yamila; Lumsden, John S.; Estrada, Mario P.; Dixon, Brian (Frontiers in Immunology, 2019)
Pituitary adenylate cyclase-activating polypeptide (PACAP) is a multifunctional neuropeptide that is widely distributed in mammals and is capable of performing roles as a neurotransmitter, neuromodulator and vasodilator. This polypeptide belongs to the glucagon/secretin superfamily, of which some members have been shown to act as antimicrobial peptides in both mammalian and aquatic organisms. In teleosts, PACAP has been demonstrated to have direct antimicrobial activity against several aquatic pathogens, yet this phenomenon has never been studied throughout a live bacterial challenge. The present study focuses on the influence of synthetic Clarias gariepinus 38 amino acid PACAP on the rainbow trout monocyte/macrophage-like cell line, RTS11, when exposed to the coldwater bacterial pathogen Flavobacterium psychrophilum. PACAP was shown to have direct antimicrobial activity on F. psychrophilum when grown in both cytophaga broth and cell culture media (L-15). Further, the ability of teleostean PACAP to permeabilize the membrane of an aquatic pathogen, F. psychrophilum, was demonstrated for the first time. The viability of RTS11 when exposed to PACAP was also observed using a trypan blue exclusion assay to determine optimal experimental doses of the antimicrobial peptide. This displayed that only concentrations lower than 0.1 µM did not have a negative impact on RTS11 survival. Interestingly, when RTS11 was pre-treated with PACAP for 24 h before experiencing infection with live F. psychrophilum, growth of the pathogen was severely inhibited in a dose-dependent manner when compared to cells receiving no pre-treatment with the polypeptide. Relative expression of pro-inflammatory cytokines (IL-1β, TNFα and IL-6) and PACAP receptors (VPAC1 and PAC1) was also analyzed in RTS11 following PACAP exposure alone and in conjunction with live F. psychrophilum challenge. These qRT-PCR findings revealed that PACAP may have a synergistic effect on RTS11 immune function. The results of this study provide evidence that PACAP has immunostimulatory activity on rainbow trout immune cells as well as antimicrobial activity against aquatic bacterial pathogens such as F. psychrophilum. As there are numerous pathogens that plague the aquaculture industry, PACAP may stimulate the teleost immune system while also providing an efficacious alternative to antibiotic use.